Alice Through the Computer Screen: a Study of Literary Reading and Writing on Digital Displays - María Goicoechea de Jorge; Pilar García Carcedo (Texto Digital)
This article presents a summary and a series of conclusions and reflectionson the digital reading and writing experiences carried out during the years 2009-2010/2010-2011, by the research group LEETHI (Spanish and European Literatures: from text to hypertext) from the University Complutense of Madrid. With the purpose of gathering data regarding the new reading habits introduced by onscreen reading, we deviced a series of experiences organized around three modes: intensive reading through the computer screen, extended reading in e-readers and tablet PCs, and creative digital reading and writing. These experiences have been collected in the work Alicia a través de la pantalla: lecturas literarias en el siglo XXI (CITA: Fundación Germán Sánchez Ruipérez) to appear soon online.